Nonlinear Mach–Zehnder interferometer with ultrabroadband squeezed light - Horoshko, D. B.; Kolobov, M.; Gumpert, F.; Shand,; Konig, F.; Chekhova, Maria V. (Journal of Modern Optics, 2020)
We study both theoretically and experimentally the interference pattern in a nonlinear Mach–Zehnder interferometer formed by two aperiodically-poled crystals, where broadband squeezed light is generated by both crystals via parametric down-conversion with a common quasi-monochromatic pump. This configuration is important for measuring the squeezing produced by the first crystal and also for measuring a small phase shift introduced by a sample between the crystals. On the basis of the approximate quantum Rosenbluth formula for each crystal we develop an analytic model for the field evolution in the interferometer. We report an experimental observation of the interference fringes, caused by the dispersion of the generated PDC waves in both crystals forming the interferometer. We observe a displacement of the interference pattern caused by a sample between the crystals and infer the phase shift within a band of 20 nm. The experimental data are in a good agreement with the predictions of the developed model, up to imperfections of the samples.
CRIS-Team Scopus Importer:2023-03-27
Keywords: nonlinear interferometer; parametric down-conversion; Squeezed states